Induksi Teknologi Otomatisasi Membran Filtrasi Air Untuk Transformasi Kesehatan Di Pesantren Mura’atul Lughat Kecamatan Martapura Kabupaten Banjar - Sudarningsih, Sudarningsih; Madihah, Husnul; Wianto, Totok; Azizah, Laela; Nabila, Nisrina (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2025)
The Mura'atul Lughat Islamic boarding school, located in the Sekumpul sub-district, Martapura District, Banjar Regency, requires clean water to ensure the survival of its residents. Bore well water and river water in this area are not suitable for consumption. However, it is not uncommon for Islamic boarding school residents to consume this water. This situation prompted the joint Community Service team from Lambung Mangkurat University and Kalimantan Islamic University Muhammad Arsyad Al Banjari to identify and implement this activity as a way to contribute science and technology to the Mura'atul Lughat Martapura Islamic boarding school. This community service activity enables the Islamic boarding school to utilize a water filtration membrane device, rendering the drilled well water fit for human consumption. Furthermore, the training activities offered can enhance the knowledge and skills of the Islamic boarding school community. We can eliminate the current costs of purchasing gallon drinking water and generate additional revenue for Islamic boarding schools by selling refillable water through membrane filtration devices. Keywords: Garbage, river environment, cleanliness